Community responses to flood risk management An empirical Investigation of the Marine Protected Areas (MPAs) in Malaysia - Masud M.M.; Sackor A.S.; Ferdous Alam A.S.A.; Al-Amin A.Q.; Abdul Ghani A.B. (Elsevier Ltd, 2023)
coastal zone; community response; empirical analysis; flood; hazard management; marine park; participatory approach; risk assessment; Malaysia